2014
DOI: 10.2466/23.25.pms.119c12z0
|View full text |Cite
|
Sign up to set email alerts
|

Training Spatial Skills in Men and Women

Abstract: Recent studies suggest that even short-term video game training may transfer to other cognitive tasks. With the popularity of the Nintendo Wii with women, more of them might be exposed to the games that will increase their mental rotation skills. Because performance on mental rotation tests (MRT) has been linked to math performance in women, and thus may ultimately contribute to the under representation of women in STEM fields, it is important to continue to explore ways to decrease or eliminate the robust sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 50 publications
3
27
0
1
Order By: Relevance
“…The length of the trainings proposed by studies included in this systematic review resulted to be rather heterogeneous, both in the number of sessions and in the number of weeks. In particular, the mean number of sessions was 10.1, ranging from 1 to 60 sessions, while the mean number of hours played was 13.5, ranging between 10 min and 50 h. As for cognitive training, a minimum of one session (e.g., Colzato et al, 2013 ; Cherney et al, 2014 ), and a maximum of 60 sessions (Kühn et al, 2014 ). The number of hours spent playing the different video games differed from study to study as well: from several minutes (Stroud and Whitbourne, 2015 ) to up to 50 h (Green et al, 2012 ; Chandra et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of the trainings proposed by studies included in this systematic review resulted to be rather heterogeneous, both in the number of sessions and in the number of weeks. In particular, the mean number of sessions was 10.1, ranging from 1 to 60 sessions, while the mean number of hours played was 13.5, ranging between 10 min and 50 h. As for cognitive training, a minimum of one session (e.g., Colzato et al, 2013 ; Cherney et al, 2014 ), and a maximum of 60 sessions (Kühn et al, 2014 ). The number of hours spent playing the different video games differed from study to study as well: from several minutes (Stroud and Whitbourne, 2015 ) to up to 50 h (Green et al, 2012 ; Chandra et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mental spatial rotation (2 studies): Enhancement of mental spatial rotation abilities was reported after training with commercial exergames and driving-racing games, with a greater advance for women (Cherney et al, 2014 ). In contrast, no improvement was observed after training with other commercial games (one exergame and several action games), probably because of the limited number of participants (Dominiak and Wiemeyer, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the sex differences found in MR visuospatial training, variable results have also been obtained. While Marulis et al’s (2007) meta-analysis indicated that the improvement in the performance of this ability is equivalent for both sexes, other studies performed on different age groups have suggested that the mean performance after a training program can be more pronounced in females, which leads to the disappearance of sex differences for such ability (e.g., Pleet, 1991 ; Boulter, 1992 ; De Lisi and Wolford, 2002 ; Sanz de Acedo Lizarraga and García Ganuza, 2003 ; Ehrlich et al, 2006 ; Wiedenbauer and Jansen-Osmann, 2008 ; Neubauer et al, 2010 ; Cherney et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, boys achieved a better performance in the MR task than girls, as a group. However, some studies have already shown that practice with video games can reduce or eliminate these sex differences in spatial skills, including MR ( Cherney, 2008 ; Cherney et al, 2014 ), and these findings encourage the motivation of females to have a greater interaction with this type of videogames.…”
Section: Introductionmentioning
confidence: 99%